2016
DOI: 10.1074/jbc.m116.749507
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Negative Cooperativity in Glutathione Transferase Enabled Preservation of Enzyme Function

Abstract: Edited by Norma AllewellNegative cooperativity in enzyme reactions, in which the first event makes subsequent events less favorable, is sometimes well understood at the molecular level, but its physiological role has often been obscure. Negative cooperativity occurs in human glutathione transferase (GST) GSTP1-1 when it binds and neutralizes a toxic nitric oxide adduct, the dinitrosyl-diglutathionyl iron complex (DNDGIC). However, the generality of this behavior across the divergent GST family and its evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…The formation of DNIC-protein complexes was previously described for bovine serum albumin [9] and for proteins of the glutathione transferase (GST) family [60,61]. The latter were extensively investigated by Ricci and co-workers, who showed that these enzymes, in particular the Tyr GSTs, have an extremely high affinity for DNIC, forming DNIC-GST complexes, whose dissociation constant attain the range of 10 −9 to 10 −12 M [62].…”
Section: Discussionmentioning
confidence: 99%
“…The formation of DNIC-protein complexes was previously described for bovine serum albumin [9] and for proteins of the glutathione transferase (GST) family [60,61]. The latter were extensively investigated by Ricci and co-workers, who showed that these enzymes, in particular the Tyr GSTs, have an extremely high affinity for DNIC, forming DNIC-GST complexes, whose dissociation constant attain the range of 10 −9 to 10 −12 M [62].…”
Section: Discussionmentioning
confidence: 99%
“…Cooperativity in BCR-ABL, a tyrosine kinase identified as a hallmark for myeloid leukaemia can be either negative [54, 55] or positive [26] depending on the coupling between the nucleotide and substrate binding sites. In CaMKII, as reported here, the nucleotide and substrate binding modules are again recruited for the formation of positive trans-subunit couplings.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism preserves GSTP1-1 from complete inactivation when it is involved in the DNDGIC detoxification, maintaining its classical conjugating activity even when an excess of NO is produced in the cell. This particular self-preservation has been also found also in other GST isoenzymes like the Alpha and Mu GSTs but not in bacterial GSTs, suggesting that this property has been acquired only in the more recently evolved organisms [25].…”
Section: Introductionmentioning
confidence: 95%